Tibetan mineral-herbal medicine Zuotai alleviates the depressive-like behaviors in chronic restraint-stressed mice while regulating stress hormone, inflammation and monoamine - Li, Cen; Niu, Cuiying; Bi, Hongtao; Zhao, Jing; Ivan Alvarez, Jorge; Yuan, Farong; Gai, Xiangyun; Wei, Lixin; Du, Yuzhi; Qiao, Yajun; Kebir, Hania; Xiao, Yuancan; et al. (Frontiers in Pharmacology, 2023)
Introduction:Zuotai is an ancient mineral-herbal mixture containing β-HgS in Tibetan medicine. It is used to treat nervous system diseases, similar to Chinese medicine cinnabar and Indian Ayurveda medicine Rasasindura. However, one of the key problems faced by Zuotai is that its indications are ambiguous. Our previous study found that Zuotai exhibited the activity of ameliorating depressive-like behaviors in a chronic mild stress model. However, due to the inherent limitations of animal models in simulating human disease, clear results often require more than one model for confirmation. Methods: Therefore, another depression model, chronic restraint stressed (CRS) mice, was used to validate the antidepression effect of Zuotai. Prophylactic treatment was conducted for 21 consecutive days while mice were subjected to chronic restraint stress. Results: It was observed that Zuotai and β-HgS alleviated anhedonia, behavioral despair, stereotype behavior, and reduced exploratory and spontaneous movement in CRS mice. Zuotai and β-HgS also reversed the increases of stress hormone corticosterone (Cort) in serum and pro-inflammatory cytokines in serum and brain, and increased the serotonin in cortex in CRS mice, with positive dose-effect relationship. The number of Ki67-positive cells in the dentate gyrus and the level of brain-derived neurotrophic factor (BDNF) in the hippocampus were slightly elevated in CRS mice treated with Zuotai; however, there was no statistically significant difference. Although Zuotai increased the total Hg concentration in main organs, the levels remained below those needed to result in observed adverse effect, at least for kidney and liver; and Zuotai showed no observed adverse effect on the brain histopathology, the cell proliferation in dentate gyrus, as well as the hippocampal and cortical organ coefficients. Conclusion:Zuotai exhibited the alleviation of depressive-like behaviors in CRS mice, accompanying with ameliorating stress hormone, peripherical and cerebral inflammation, and monoamine neurotransmitter.